2017
DOI: 10.4172/pharmaceutical-sciences.1000238
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Studies of Earthworm Fibrinolytic Enzyme Component A from Eisenia foetida on Breast Cancer Cell Line MCF-7

Abstract: Liu, et al.: Antitumor Studies of Earthworm Fibrinolytic Enzyme Component A on MCF-7Earthworm fibrinolytic enzyme from Chinese earthworm Eisenia foetida was isolated to investigate its antitumor activity in breast cancer cells. The protein isolated was characterised as earthworm fibrinolytic enzyme using the fibrin plate method. The molecular weight of earthworm fibrinolytic enzyme component was determined to be 25 kDa by sodium dodecyl sulfate polyacrylamide gel electrophoresis assay using a standard protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Earthworm coelomic fluid and extracts showed antibacterial and antifungal activities (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) as well as antiviral action (18). Earthworm tissues, extracts, or isolated fractions and compounds exhibited anticancer activity toward different cancer cell lines (19)(20)(21)(22)(23)(24)(25)(26). The development of research on the antimicrobial activity in earthworms has gained momentum over the last few years, while the anticancer activity has been reported in few studies.…”
mentioning
confidence: 99%
“…Earthworm coelomic fluid and extracts showed antibacterial and antifungal activities (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) as well as antiviral action (18). Earthworm tissues, extracts, or isolated fractions and compounds exhibited anticancer activity toward different cancer cell lines (19)(20)(21)(22)(23)(24)(25)(26). The development of research on the antimicrobial activity in earthworms has gained momentum over the last few years, while the anticancer activity has been reported in few studies.…”
mentioning
confidence: 99%
“…Coelomic fluid has been known to be used as a therapy for several diseases because it has anti-inflammatory, antioxidant, antibacterial, and antitumor effects [7]. Biological substances contained coelomic fluid including lectin [8] and earthworm fibrinolytic enzyme also known as lumbrokinase [26,29,30]. Lectins have been proven to be used as anticancer in the MCF-7 cell line via the MAPK pathway by targeting EGFR to induce cell apoptosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro and in vivo study has shown that earthworm fibrinolytic enzyme component A from Eisenia fetida could effectively inhibit the proliferation of MCF-7 cells. Another study showed that earthworm fibrinolytic enzyme has significant antitumor activity by inhibiting the expression of matrix metalloproteinase-2 (MMP-2) [30]. MMP-2 (gelatinase A) and MMP-9 (gelatinase B) are both cancer associated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations